Collaboration between non-governmental organizations and educational leaders in capacity development in rural South Africa - Ayehsabu, Ayuk (2013)
Skills development has been a point of urgency since the advent of progressive governance in democratic South Africa. Despite many efforts through the National Skills Development Strategies and partnerships, the situation still remains worrisome especially in rural context. The study aimed to identify how the NGOs and education leaders collaborate in skills development, its impact, and possible ways of optimizing such practices. A methodology that considers the perspectives of individuals experiencing the phenomenon was invoked. Accordingly, this study exploits the phenomenological approach. Participants were purposely selected from Sector Education Training Authorities and NGOs involved in Education and Training. Triangulation was also used due to the inclusion of the third kind of participants. Nine participants from five organizations were involved. Data was collected through in-depth phenomenological unstructured interviews and analyzed with the use of phenomenological analytic methods. Findings indicated participants’ awareness of the importance of skills development to rural dwellers, and have experienced collaboration through research and other modes, with impressive effects. However, there is great need to strengthen collaboration. Lack of Strategic leadership including strategic partnership practices, and poor rural schooling were the weakest link in skills development initiatives. The study culminated with recommendations aimed at circumventing such problems, enhance skills development, and foster human security in rural areas. It was limited to skills development; hence similar studies on institutional development would be fascinating.